THE OPTIMAL CONTROL IN THE MODELOF NETWORK SECURITY FROM MALICIOUS CODE - N. F. Semykina (Научный вестник МГТУ ГА)
The paper deals with a mathematical model of network security. The model is described in terms of the nonlinear optimal control. As a criterion of the control problem quality the price of the summary damage inflicted by the harmful codes is chosen, under additional restriction: the number of recovered nodes is maximized. The Pontryagin maximum principle for construction of the optimal decisions is formulated. The number of switching points of the optimal control is found. The explicit form of optimal control is given using the Lagrange multipliers method.